Experimental Irish Theatre - Walsh, I. author. aut Link
VIII, 202 p.
Keywords: This book examines experimental Irish theatre that ran counter to the naturalistic 'peasant' drama synonymous with Irish playwriting. Focusing on four marginalised playwrights after Yeats, it charts a tradition linking the experimentation of the early Irish theatre movement with the innovation of contemporary Irish and international drama.